2020
DOI: 10.1016/j.landusepol.2019.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Resettlement preferences from landslide prone areas in Cameroon: Willingness to move, reasons to stay

Abstract: Resettlement as a disaster risk reduction strategy entails a threat for livelihoods Individual resettlement preferences show heterogeneity, linked to wealth Poor households attach importance to their social network There is a mismatch between group behavior and individual preferences Trust, group behavior and historical events are therefore important for resettlement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…In that case, it will inevitably result in or intensify the worsening of the ecological environment and geological disasters, thus posing an increased threat to the life and property of residents. Previous studies have found that the intention of peasant households plays an essential role in the spatial reconstruction of rural settlements [12,40,93]. Government-guided rural planning often fails if it does not respect the intention of peasant households and forces them to move [28,94,95].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, it will inevitably result in or intensify the worsening of the ecological environment and geological disasters, thus posing an increased threat to the life and property of residents. Previous studies have found that the intention of peasant households plays an essential role in the spatial reconstruction of rural settlements [12,40,93]. Government-guided rural planning often fails if it does not respect the intention of peasant households and forces them to move [28,94,95].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the driving forces for the spatial reconstruction of rural settlements have mainly concentrated on plain regions; however, there are few that have involved mountainous regions and hills [35][36][37][38]. The most common measurement models that have been used to study the driving forces for the spatial reconstruction of rural settlements are the Probit and Logit models [29,39,40]. Recently, structural equation modeling (SEM) [41] has also been applied to this area.…”
Section: Introductionmentioning
confidence: 99%
“…House owners prefer thorough retrofitting, compared to apartment renters, who prefer low-cost, temporary retrofitting (Gupta and Gregg, 2012). This heterogeneity depends on the targeted socio-economic groups and their preferences, access to roads, the use of social networks or trust in governments (Baert et al, 2019). Moreover, piecemeal approaches fail in LRR.…”
Section: Community Willingness To Invest In Lrrmentioning
confidence: 99%
“…When Vlaeminck study the willingness to re-settle from landslide prone areas in Uganda, they find that people living in high risk areas (on steep slopes or in villages that have already been affected by landslides) are more willing to re-settle than people living in low-risk areas (Vlaeminck et al, 2016). It has also been found that wealthier households are more willing to re-settle than poorer households and that institutional factors such as trust in institutions are important for the willingness to re-settle in Cameroon (Baert et al 2020).…”
Section: Introductionmentioning
confidence: 99%